1981
DOI: 10.3109/15563658108990355
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Disulfide Neuropathy in Rats. A Morphological and Ultrastructural Study of Degeneration and Regeneration

Abstract: The aim of this study was to elucidate the site and detailed nature of peripheral nerve damage induced in the rat by chronic CS2 inhalation exposure in the light of the relationship between pathological and neurophysiological data. Adult male rats were exposed to 700 ppm of CS2 2 h/d, 5 d/week for 12 weeks and then followed-up for 18 weeks. The first alteration observed was a decrease in the nerve conduction velocity, discovered after only 3 weeks of exposure. Pathological lesions were first observed in the 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…But it is to be noted that maneb, zineb, and propineb are reported to be cytotoxic for mammalian cells only at a concentration which is at least 50 times higher than their antileishmanial LD 50 s (48,49). Similarly, the neuropathic effects of carbon disulfide-or ethylene thiourea-induced thyroid tumors were observed in rats after chronic exposure to a very high dose of these compounds (e.g., when exposed to 700 ppm or 9.19 mM carbon disulfide for 2 h/day, 5 days/week for 12 weeks or fed with Ͼ250 ppm or 2.44 mM ethylene thiourea in the diet for 2 years) (50,51). So, the submicromolar doses at which these metal dithiocarbamates are effective against the parasites should be safe for the mammalian cells.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…But it is to be noted that maneb, zineb, and propineb are reported to be cytotoxic for mammalian cells only at a concentration which is at least 50 times higher than their antileishmanial LD 50 s (48,49). Similarly, the neuropathic effects of carbon disulfide-or ethylene thiourea-induced thyroid tumors were observed in rats after chronic exposure to a very high dose of these compounds (e.g., when exposed to 700 ppm or 9.19 mM carbon disulfide for 2 h/day, 5 days/week for 12 weeks or fed with Ͼ250 ppm or 2.44 mM ethylene thiourea in the diet for 2 years) (50,51). So, the submicromolar doses at which these metal dithiocarbamates are effective against the parasites should be safe for the mammalian cells.…”
Section: Discussionmentioning
confidence: 94%
“…These compounds were also highly cytotoxic for the parasite as evident from the MTT assay. The submicromolar LD 50 values of these metal dithiocarbamates (0.56 M for maneb, 0.61 M for zineb, and 0.27 M for propineb) indicate that their in vitro leishmanicidal activity is comparable to that of amphotericin B, which is thus far the most potent antileishmanial drug (36). The heterocyclic thiols are the only known CA inhibitors reported to exhibit antileishmanial activity.…”
Section: Discussionmentioning
confidence: 98%
“…It was shown that the functional and histopathological signs of muscle weakness were completely reversible within 14 days (Jones 1999;Pauluhn , 2001. Recovery from a CS 2 -induced neurodegeneration after repeated-dose experiments will take months (Clerici and Fechter 1991;Colombi et al 1981). Again, it seems plausible that the effects in our present study were mediated by zinc toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…This improved after that time, and function was near normal by the end of the 4-month recovery period. 24 This carbon disulfide study shows peripheral nerve myelinated fiber degeneration featuring axonal lesions progressing to fiber breakdown during and shortly after toxicant exposure, with regeneration seen following a period of recovery. In a similar study, Jirmanová and Lukáš 25 exposed adult Wistar rats to carbon disulfide vapor at 2.4 mg/L of air for 5 d/wk, 6 h/d for 6 months, and saw similar axonal lesions characterized by giant axonal swellings related to disorganized masses of neurofilaments.…”
Section: Regeneration Following Toxic Peripheral Neuropathymentioning
confidence: 84%